Diversity in bilingual child language acquisition research: A commentary on Kidd and Garcia (2022). Issue 6 (December 2022) - Rochanavibhata, Sirada; Marian, Viorica
Kidd and Garcia report that language acquisition studies are skewed toward monolingual and English-speaking populations. This commentary considers Kidd and Garcia's arguments in light of our research on mother-preschooler discourse and non-verbal communication in Thai monolingual and Thai-English bilingual children. We discuss lessons learned from testing linguistically diverse children and underscore the importance of research on non-WEIRD (Western, Industrialized, Educated, Rich, and Democratic) populations. We advocate for the inclusion of children who speak understudied languages and those who speak multiple languages in developmental science.